Clinical Significance of LINC00261 in the Pathogenesis of Pancreatic, Colorectal, Hepatocellular, and Gallbladder Cancer - Sanjana Bana; Sia Daffara; Aastha Dagar; Ashutosh Kumar Tiwari; Kanupriya Medhi; Sagarika Mukherjee; Vivek Uttam; Md Rizwan Ansari; Hardeep Singh Tuli; Vikas Yadav; Aklank Jain (Diseases)
Pancreatic (PC), colorectal (CRC), hepatocellular (HCC), and gallbladder (GC) cancers together account for nearly 20% of all cancer cases. However, specific biomarkers and therapeutic targets for these cancers are lacking. Diagnosing these cancers early and providing timely, appropriate treatment to improve patient outcomes is crucial. In this context, previous studies, including ours, have highlighted the potential of non-coding RNAs, particularly long non-coding RNAs (lncRNAs), in diagnosing and prognosis of various cancers. This review focuses on the mechanistic role of the recently identified lncRNA LINC00261 in PC, CRC, HCC, and GC. Our comprehensive literature analysis revealed that LINC00261 functions as a tumor suppressor, and its reduced expression is associated with larger tumor size, advanced tumor-node-metastasis (TNM) stages, lymphatic metastasis, and poorer overall survival rates. Additionally, we discovered that LINC00261 acts as a molecular sponge for miRNAs, such as miR-550a-3p, miR-23a-3p, miR-148a, miR-324-3p, and miR-105-5p, regulating critical cancer-related signaling pathways, including PI3K/Akt/mTOR, Protein kinase B, and Mammalian target of rapamycin (mTOR). Further bioinformatic analysis revealed that LINC00261 regulates key cellular processes, such as protein-DNA complex formation, ribonuclease complex activity, histone deacetylase complexes, and nuclear matrix interactions. Overall, we believe that LINC00261 holds significant promise as a future biomarker and, when combined with existing treatment strategies, may enhance cancer patient care and survival.